Exploring The Teacher Agency Regarding to The Implementation of Flipped-Differentiated Learning in The Context of EFL Learners - Kristoforus Gustian; Istanti Hermagustiana; Dyah Sunggingwati (Journal on Education, 2023)
The purpose of this study is to present a qualitative case study that investigates teacher agency in the context of implementing Flipped-Differentiated Learning (FDL) for English as a Foreign Language (EFL) learners. The study included two participants who used the FDL approach, and their experiences were investigated to learn how their agency changed during the process. Prior to implementation, both teachers were concerned about implementing this novel approach. The findings of the study show that, despite early limits, teachers were able to acquire a sense of agency when they applied FDL in their EFL classrooms. Throughout the study, they demonstrated increasing confidence in their teaching judgments and involvement with students. This newfound agency allowed teachers to adjust their teaching approaches to better suit their students' different needs and learning styles, resulting in improved learning outcomes. However, the study also shows a gap in existing evidence about the relationship between teacher agency and FDL implementation. While the research gives useful insights into the transformative potential of FDL on teacher agency, more research is needed to establish a thorough grasp of this correlation. Future research should focus on filling this vacuum and delving deeper into the mechanisms through which FDL influences teacher agency, ultimately contributing to the refinement and optimization of flipped-differentiated learning practices in EFL contexts.